(untitled) (Damu Journal of Sport Sciences, 2025)
The importance of the research came to emphasize the importance of motor learning and its correct and logical theories and its role in learning skill performance with foil as it helps the learner to advance the skill aspect, as well as helps us in building an educated and creative generation in performance in the future during various tournaments and competitions. Raising the level of learning for skill performance in foil requires us to develop exercises that are purposeful and based on scientific foundations, including motor learning theories, as each theory achieves the goals set in its construction and helps to learn an aspect of the idea for which this theory was developed. This is considered the research problem that was discovered through the researcher's modest experience in motor learning and fencing, that learning skill performance in foil does not rise to the level of ambition, which is due to the lack of use of the appropriate learning theory in education. This is what made the researcher investigate the facts of the closed theory in learning and its role in learning basic skills in foil. The most important objectives of the research were: Identifying the effect of closed circuit educational exercises in teaching basic offensive skills in foil for beginners. - The research sample included: Third-year students in the College of Physical Education and Sports Sciences - University of Basra. The most important conclusions were reached: Educational exercises according to the closed circuit theory have a major role in the process of learning some basic offensive skills in foil due to its successful scientific characteristics. The researcher recommended: adopting educational exercises according to the closed circuit theory, due to its major role in the process of learning some offensive skills with foil, and due to its successful scientific characteristics.